Everfound book 3 of the skinjacker trilogy - Shusterman, Neal (Shusterman, Neal. Skinjacker trilogy, 2011)
In the limbo that's Everlost, Mary, Nick, Allie, and others face the decisions that will determine whether that place and the Earth itself will continue to exist, as well as where their own futures lie.